PERAN PEMERINTAH DESA DALAM INTERNASIONALISASI DESA WISATA SEKAPUK DI KECAMATAN UJUNGPANGKAH GRESIK - Wati, Widya; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
The desire to establish a tourist village aims to empower the community to play a role in increasing the potential and attractiveness of tourism in their area. This study was conducted to describe the role of the village government in developing Setigi tourism in Sekapuk Village into an international tourist village. Qualitative research approach. The focus of the study is the role of the village government in internationalizing the Sekapuk tourist village. The research location is in Sekapuk Village, Ujungpangkah District, Gresik. The research subjects were five people consisting of Abdul Halim, Mundhor, M. Lutfi Tsalis Af Hami, Asjudi, and M. Ubaidillah. Data were collected through observation and in-depth interviews. The data analysis technique used the Miles and Huberman technique through four stages of data collection, data reduction, presentation and drawing conclusions correlated with the theory of the role of the village government according to Blakely. The results of the study show that the village government, BUMDesa Sekapuk, Pokdarwis Pelangi, the Miliader Village Training Center (PDDM) and BPD have succeeded in building and introducing the Sekapuk tourist village through the famous Setigi tourism in world tourism. The purpose of building the Setigi tourism which utilizes the former limestone mining land has succeeded in opening up employment opportunities for the Sekapuk community so that it has received appreciation from various ministries and several countries. The Ministry of Villages, Development of Disadvantaged Regions and Transmigration (PDTT) chose the Sekapuk tourism village to represent Indonesia to become part of an international organization. Activities carried out by the village government during the development of the Sekapuk tourism village include preparing human resources, participating in various tourism village competitions, and attending international organization conferences.